Assessing the Energy Performance of Public University in Malaysia by using Energy Conservation Measure (ECM): A Case Study of UiTM Tapah, Malaysia - Ahmad, Nur Azfahani; Dzulkefli, Muhammad Hilmi; Abdul Rahim, Fiza (International Journal of Sustainable Construction Engineering and Technology, 2023)
The growth of energy consumption in Malaysian universities has elevated national concern because it increases government annual expenditure and at the same time influence the national energy performance. In managing the energy performance of universities, it is significant to monitor the energy usage whereby areas and facilities that have the potential for energy savings can be audited in order to obtain energy-efficiency. The objective of this research is to focus on the energy performance processes conducted by identify and evaluate a various of the Energy Conservation Measure (ECM) that may contribute towards energy efficiency in the public universities. ECM has been used to acquire achievable solutions and improvement of energy consumption during the energy audit. A related information on energy audit, like electrical and mechanical systems specifications have been compiled and the use of energy have been profiled. A potential finding method used was a comparative analysis between energy implementation process before and after audit. It has been found that the significant processes in an energy audit can help to save energy consumption by comparing the energy implementation process. It is done through an investigation of energy consumption behaviour in the ECM process for the electrical and mechanical systems, and buildings activities that have an impact on energy consumption which allow energy-efficiency in a building. A case study of UiTM in Tapah Campus, Malaysia has been selected for this research since this university is among new public university in Malaysia that has higher energy users.  It has been found that with the aid of ECM, this university will be able to achieve 135 kWh/m2/year of Building Energy Index (BEI). Eight (8) improvement strategies in ECMs have been suggested that significantly achieve the energy performance efficiency, involving eight (8) strategies, which are four (4) No-Cost Measures, two (2) Medium-Cost Measures and two (2) High-Cost Measures.